Identification of α‐Mangostin as an Agonist of Human STING. (30th August 2018) - Zhang, Yibo; Sun, Zhen; Pei, Jianwen; Luo, Qinhong; Zeng, Xin; Li, Qinkai; Yang, Zhen; Quan, Junmin
Abstract: The xanthone derivate 5′, 6′‐dimethylxanthenone‐4‐acetic acid (DMXAA, also known as ASA404 or vadimezan) is a potent agonist of murine STING (stimulator of interferon genes), but cannot activate human STING. Herein we report that α‐mangostin, which bears the xanthone skeleton, is an agonist of human STING, but activates murine STING to a lesser extent. Biochemical and cell‐based assays indicate that α‐mangostin binds to and activates human STING, leading to activation of the downstream interferon regulatory factor (IRF) pathway and production of type I interferons. Furthermore, our studies show that α‐mangostin has the potential to repolarize human monocyte‐derived M2 macrophages to the M1 phenotype. The agonist effect of α‐mangostin in the STING pathway might account for its antitumor and antiviral activities. Abstract : Putting the STING on cancer : Herein we report α‐mangostin as an agonist of human STING. α‐Mangostin binds to human STING and activates the downstream TBK1‐IRF3 cascade to promote the production of type I interferon. Furthermore, α‐mangostin has the potential to re‐educate human monocyte‐derived M2 macrophages to the M1 phenotype.